2016
DOI: 10.1080/09540121.2016.1192577
|View full text |Cite
|
Sign up to set email alerts
|

Factors of interpersonal communication and behavioral health on medication self-efficacy and medication adherence

Abstract: Despite devastating effects on health outcomes and disease progression, many people living with HIV (PLWH) are non-adherent to their medications. Medication self-efficacy is a pivotal factor in medication adherence, yet its formation and relationship with other factors are understudied. This study examines a model that considers the role of three communicative factors (patient-provider communication, social support, and social undermining) and two behavioral health factors (depression and alcohol abuse) and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…This study is among the first to examine the mediational influence of self-efficacy on the relationship between depression and stigma with ART adherence among youth particularly in SSA. The current findings are consistent with previous studies among adult samples that found that self-efficacy mediates the relationship between depression and stigma with ART adherence (Cha, Erlen, Kim, Sereika, & Caruthers, 2008;Archiopoli, et al, 2016;Seghatol-Eslami, 2017). Depression and stigma appear to influence ART adherence through their effect on youth's self-efficacy with respect to medication.…”
Section: Discussionsupporting
confidence: 92%
“…This study is among the first to examine the mediational influence of self-efficacy on the relationship between depression and stigma with ART adherence among youth particularly in SSA. The current findings are consistent with previous studies among adult samples that found that self-efficacy mediates the relationship between depression and stigma with ART adherence (Cha, Erlen, Kim, Sereika, & Caruthers, 2008;Archiopoli, et al, 2016;Seghatol-Eslami, 2017). Depression and stigma appear to influence ART adherence through their effect on youth's self-efficacy with respect to medication.…”
Section: Discussionsupporting
confidence: 92%
“…Rather than any particular disease feature, it was simply self-confidence in their own ability to take β-blockers and their belief as to how essential the medication was which were the strongest predictors of adherence. These findings are consistent with previous research across different health conditions, ages and cultures,18–21 and present a significant opportunity to intervene and improve adherence. For a start, a simple question enquiring about the patient’s own beliefs as to their ability to adhere to therapy will help to find patients who need additional support with their medication regimen.…”
Section: Discussionsupporting
confidence: 91%
“…The reduction in complication rates seen in our study may be due to increased patient compliance to postoperative protocols, which was augmented by increased provider-patient interaction [37] , [38] . This association between patient communication and preventable adverse events has been described by Barlett et al.…”
Section: Discussionmentioning
confidence: 70%